2018
DOI: 10.1101/cshperspect.a030403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology of High-Grade Prostatic Intraepithelial Neoplasia: Challenges and Opportunities

Abstract: A better understanding of the early stages of prostate cancer initiation, potentially arising from precursor lesions, may fuel development of powerful approaches for prostate cancer prevention or interception. The best-known candidate for such a precursor lesion has been referred to as high-grade prostatic intraepithelial neoplasia (HGPIN). Although there is significant evidence supporting the notion that such HGPIN lesions can give rise to invasive adenocarcinomas of the prostate, there are also numerous comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 116 publications
0
31
0
Order By: Relevance
“…Morphologically, our series of iIDC-P strongly implicates a subset of IDC-P as a distinct in situ lesion and one that may precede the development of high-grade invasive disease. HGPIN is currently the only accepted precursor lesion to invasive PCa, with a preponderance of morphologic and molecular evidence supporting this notion [41][42][43]. However, two of our prior studies and one by Miyai et al reported IDC-P in the absence of, or regionally separate from, high-grade invasive carcinoma (i.e.…”
Section: Discussionmentioning
confidence: 78%
“…Morphologically, our series of iIDC-P strongly implicates a subset of IDC-P as a distinct in situ lesion and one that may precede the development of high-grade invasive disease. HGPIN is currently the only accepted precursor lesion to invasive PCa, with a preponderance of morphologic and molecular evidence supporting this notion [41][42][43]. However, two of our prior studies and one by Miyai et al reported IDC-P in the absence of, or regionally separate from, high-grade invasive carcinoma (i.e.…”
Section: Discussionmentioning
confidence: 78%
“…These observations suggest that the HGPIN lesion adjacent to invasive carcinoma does not necessarily represent its respective precursor lesion and additional studies based on single-cell molecular analysis and lineage tracing studies are required to define such a relationship [7]. Furthermore, recent studies have suggested that some HGPINs are in fact invasive prostate cancers masquerading as a HGPIN-like condition [19].…”
Section: Tumor Evolution Of Prostate Cancer From Precursor Lesionsmentioning
confidence: 99%
“…In spite all the limitations in the definition and identification of precursor lesions of prostate cancer, the search of prostate cancer precursors lesions is of fundamental importance because offers the unique opportunity for disease prevention and treatment [19].…”
Section: Tumor Evolution Of Prostate Cancer From Precursor Lesionsmentioning
confidence: 99%
“…We analytically validated an automated IHC assay against human GSTP1 protein using well-known cell lines and controls and human prostate cancer tissues (8) . Cell line FFPE blocks were prepared and utilized as described (29,30) .…”
Section: Ihc Stainingmentioning
confidence: 99%
“…We developed a novel in situ hybridization assay for GSTP1 mRNA using ACD RNAscope, which we analytically validated (Probe-Hs-GSTP1 Cat No. 453221, kit version 2.5 manual assay according to manufacturer's recommendations) using cell lines with known GSTP1 expression status for positive and negative controls as described (8) .…”
Section: In Situ Hybridization For Gstp1 Mrnamentioning
confidence: 99%